EFFECT OF SOME NUTRIENTS MANAGEMENT PRACTICES AND LEACHING REQUIREMENTS ON SOIL QUALITY AND PRODUCTIVITY OF SORGHUM GROWN IN A SALT -AFFECTED SOIL - Hameed, Marwan A; Ali, Nooruldeen S.; Karim, Hadi M (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
A field experiment was conducted at the research station of the Ministry of Agriculture in Abu Ghraib area –Baghdad, Iraq, to study the effect of applying some nutrients management practices and leaching requirements on some soil quality indicators and sorghum productivity under saline soil conditions. The experiment was laid out in randomized complete block design )RCBD( with split split plot arrangement and three replicates. Treatments included 7 nutrients combinations :(Control” F0”, NPK” F1”, NPKS” F2”, NPKS + micronutrients”F3”, NPKS+ micronutrients+ Nano silicon” F4”, NPKS+ micronutrients + Nano silicon + calcium and magnesium nitrate” F5”, NPKS + micronutrients + Nano silicon + potassium humates” F6”, two leaching requirements: standard leaching requirements (L1) and doubled leaching requirements (L2) ) and two sorghum varieties: Al-Khair synthetic variety (C1) and Rabeh synthetic variety(C2). The results showed that fertilizer treatments had a very important role in the availability of nutrients in the soil, where treatment F6 exceeded other treatments in flowering stage in increase the availability of (N,P and Si) (48.0, 32.43and 17.45 mg Kg-1) respectively, as well as in after harvest stage treatment F6 exceeded the other treatments in increase the availability of (N,K,Fe and Si) (26.9, 293.8, 3.21 and 15.49 mg Kg-1) respectively. Doubled leaching requirements (L2) exceeded (L1), which led to reducing the amount of NaCl salts in the soil for the depth of (25-50 cm). Proper nutrients management practices could improve soil properties, increase the availability of nutrients, and improve plant tolerance to abiotic stress such as soil salinity.